High-flow nasal cannula improves respiratory impedance evaluated by impulse oscillometry in chronic obstructive pulmonary disease patients: a randomised controlled trial - Yen-Liang Kuo; Chen-Lin Chien; Hsin-Kuo Ko; Hsin-Chih Lai; Tzu-Lung Lin; Li-Na Lee; Chih-Yueh Chang; Hsiang-Shi Shen; Chia-Chen Lu (Scientific Reports, 2022)
Abstract Non-pharmacological treatment with high-flow nasal cannula (HFNC) may play a vital role in treatment of patients with chronic obstructive pulmonary disease (COPD). To evaluate the efficacy of HFNC, impulse oscillation system (IOS) is a new noninvasive technique in measuring the impedance of different portions of lungs. It shows higher sensitivity in contrast to conventional pulmonary function tests (PFT). However, whether IOS is an appropriate technique to evaluate the efficacy of HFNC in improving the impedance of small airways or peripheral lung in patients with COPD is still unclear. We enrolled 26 stable COPD participants randomised into two groups receiving HFNC or nasal cannula (NC) for 10 min followed by a 4-week washout period and crossover alternatively. IOS was used to detect the difference of respiratory impedance after HFNC or NC interventions. IOS parameters, PFT results, transcutaneous partial pressure of carbon dioxide, peripheral oxygen saturation, body temperature, respiratory rate, pulse rate, and blood pressure at the time of pre-HFNC, post-HFNC, pre-NC, and post-NC, were collected and analysed using SPSS (version 25.0, IBM, Armonk, NY, USA). The IOS measurement indicated that HFNC significantly improved R5, R5% predicted, R5–R20, X5-predicted, and Fres compared with NC, whereas no significant difference was observed through the PFT measurement. The beneficial effect of HFNC in improving small airway resistance and peripheral lung reactance compared with that of NC in patients with stable COPD was confirmed through IOS measurement. Trial registration: ClinicalTrials.gov NCT05130112 22/11/2021.